Visualization of convective plasma cells in 2D - Carboni, Rodrigo; Frutos Alfaro, Francisco (Ciencia)
Computer simulations of plasmas are relevant nowadays, because it helps us understand physical processes taking place in the sun and other stellar objects. We developed a program, called XPCell, which is intended for displaying the evolution of the magnetic field in a 2D convective plasma cell with perfect conducting walls for different stationary plasma velocity fields. Applications of this program are presented. This software works interactively with the mouse via a graphical user interface. XPCell graphical user interface was generated with XForms. For displaying the simulations, XPCell uses free version of OpenGL, which is available for all computer systems. This software allows the user to create movies in MPEG and AVI format.